Distortionary, non-distortionary, and distributional properties of environmental taxes: Extension of Sandmo's observation - Talbot Page; Qinghua Zhang (Brown University, Department of Economics, 2003)
We find a limited parallel between lump-sum taxes and environmental taxes. Corollary 2, which extends Sandmo's observation, shows that appropriated corrective revenues have the same non-distortionary effects as lump-sum taxes, the result reducing to the original observation when the appropriated corrective revenues meet the revenue need and achieve first-best efficiency with other taxes set at zero. Corollary 1 finds that when the corrective part of environmental taxes is used as marginal damage compensation, the non-corrective part is distortionary and symmetric with ordinary proportional labor taxes in second-best equilibria. The extension of Sandmo's observation suggests that environmental taxes may be among the least distortionary taxes in the tax system.
Keywords: D58; D62; H23; L51; Q2; Q48; 330; Environmental taxes; Pigovian taxes; Lindahl prices; second-best taxes; distortionary taxes; lump-sum taxes; Ökosteuer; Steuerwirkung; Steuerinzidenz; Theorie